Quantitative estimation of mercury intake by toxicokinetic modelling based on total mercury levels in humans. (May 2018) - Abass, K.; Huusko, A.; Knutsen, H.K.; Nieminen, P.; Myllynen, P.; Meltzer, H.M.; Vahakangas, K.; Rautio, A.
Abstract: Mercury is a toxic metal that can be disseminated into the environment from both natural and anthropogenic sources. Human exposure to the metal stems mainly from food, and more particularly from the consumption of fish and other seafoods. Examining dietary exposure and measuring mercury levels in body tissues are two ways of estimating exposure to mercury. In this study, we utilized a modelling system consisting of three linear toxicokinetic models for describing the fate of methyl mercury, inorganic mercury, and metallic mercury in the body, in order to estimate daily intake of mercury as measured through total mercury concentrations in the blood. We then compared the results stemming from our modelling system to those of the detailed semi-quantitative food frequency questionnaire (FFQ) of the Norwegian Fish and Game (NFG) Study, a project that focused on dietary mercury exposure. The results indicate that toxicokinetic modelling based on blood levels gave higher daily intake values of mercury compared to those of the FFQ. Furthermore, the former had a wider range of estimates than the latter. The properties of the toxicokinetic model or limitations in the dietary exposure assessment could be posited as reasons for the differences between the respective methods. Moreover, the results may have been influenced by sources of mercury exposure that cannot be described as dietary, such as amalgam fillings. Highlights: Total mercury in blood was employed to estimate daily intake of mercury. A modelling system based upon three linear toxicokinetic models was utilized. Toxicokinetic modelling suggested a higher daily intake than the FFQ.